Introduction: Open Dialogue around the world – implementation, outcomes, experiences and perspectives - Mosse, David; Pocobello, Raffaella; Saunders, Rob; Seikkula, Jaakko; von Peter, Sebastian (Frontiers in Psychology, 2023)
This introduction sets out the significance and scope of current research on Open Dialogue, an alternative approach to psychiatric crisis and serious mental illness that reorients psychiatry from its conventional diagnostic to a dialogical approach. The article establishes the context for contributions to the Frontiers Research Topic, ‘Open Dialogue Around the World – Implementation, Outcomes, Experiences and Perspectives.’ It explains why this is a good moment to bring together international research on Open Dialogue as the approach expands across countries, sites and services. The different designs and methodologies of Open Dialogue research are indicated, as well as the scale and focus of studies. These range from comparative surveys, organisational studies and randomised controlled trials to those examining therapeutic processes and bringing ethnographic, phenomenological and philosophical perspectives to bear on Open Dialogue.